Nutritive Value of Pleurotus eryngii (DC. ex Fr.) Quel. var. eryngii Grown on Various Agro-Wastes - Akyuz, Mehmet; Kirbag, Sevda (Univ Philippines Los Banos, 2009)
The nutritive value of Pleurotus eryngii var. eryngii grown on various agro-wastes was determined. Dry matter, moisture, crude ash, protein, fat and organic matter were 91.1-92.8, 7.24.9, 4.8-6.7, 13.6-29.9, 0.3-2.9 and 85.1-97.4% dry weight, respectively. Crude ash, protein and fat contents varied significantly, the lowest protein content was obtained with wheat straw (13.6%), whereas the highest was obtained in the mixture of wheat-soybean straw (1:1) + 20% rice bean (29.9%). Minimum fat level was 0.3% in wheat straw (WS) and maximum was 2.9% obtained in wheat straw- soybean straw (WS-SS) (1:1). There were no significant differences in dry matter, moisture and organic matter content for P. eryngii var. ferulae grown on different agricultural wastes. The difference between the obtained values may be due to the biological structure of substrates and additive material. In order to enrich the value of protein in species of mushroom growth in culture, a 1:1 ratio of the compost should be used.
Keywords: agricultural wastes; food; malnutrition; mushroom; P. eryngii var. eryngii; protein